2007
DOI: 10.1109/tmi.2007.893344
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Quantification of Atherosclerotic Plaque in CT Considering Partial Volume Effect

Abstract: Abstract-Coronary artery calcification (CAC) is quantified based on a computed tomography (CT) scan image. A calcified region is identified. Modified expectation maximization (MEM) of a statistical model for the calcified and background material is used to estimate the partial calcium content of the voxels. The algorithm limits the region over which MEM is performed. By using MEM, the statistical properties of the model are iteratively updated based on the calculated resultant calcium distribution from the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 23 publications
0
21
1
Order By: Relevance
“…An average error of 9.5% with a standard deviation of 5-20% was achieved on a cardiac phantom. However, as Dehmeshki et al [28] used a 16-slice CT system and some CT protocols that were not completely defined, a direct comparison with our results was not feasible.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…An average error of 9.5% with a standard deviation of 5-20% was achieved on a cardiac phantom. However, as Dehmeshki et al [28] used a 16-slice CT system and some CT protocols that were not completely defined, a direct comparison with our results was not feasible.…”
Section: Discussionmentioning
confidence: 73%
“…Dehmeshki et al [28] proposed another approach for the volume measurement of calcified plaques. Their algorithm used a modified expectation maximization of a statistical model for the plaque volume measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Since the intensity values of bone, especially for cortical bone, are statistically higher than the intensity of the surrounded tissue, an intensity threshold can be detected such that the intensities of most pixels of bone are greater than the threshold value, so global threshold is a commonly used method in the automated segmentation of bone from CT images [4]. However, due to the narrow inter-bone regions as well as weak and diffused boundaries in pelvis and femur, it is seldom possible to find a threshold that is less than values of all bone and greater than values of all other tissues.…”
Section: Comparison With Global-threshold Segmentationmentioning
confidence: 99%
“…However, clinical complications such as osteoarthritis and congenital deformities, technical limitations of CT imaging like inherent blurring and partial volume effect, and the narrow interbone regions and the presence of blood vessels in the bone tissues often result in textured regions, as well as weak and diffused boundaries in pelvis and femur images. Threshold-based techniques have been widely used in segmentation of the bone from CT images [2]- [4]. This type of segmentation is fairly successful in general since the CT values of bone are greater than those of the surrounding soft tissues.…”
Section: Introductionmentioning
confidence: 99%
“…However, the role seems to be largely underused, especially in Europe. Basically, the historic coronary calcium score (CCS) described by Agatston et al [20] is still the reference despite reported convincing improvements both in the detection and in the quantification processes [21,22]. The use of the CCS is mainly justified by the extensive literature and evaluation of the method during the last decades.…”
Section: Global Cardiovascular Risk Stratificationmentioning
confidence: 99%